Shari Lewis and Lamb Chop : the team that changed children's television - Segaloff, Nat; Lewis, Mallory (University Press of Kentucky, 2022)
"For almost half a century, celebrated ventriloquist and entertainer Shari Lewis delighted generations of children and adults with the help of her trusted sock puppet sidekick Lamb Chop. For decades, the beloved pair were synonymous with children's television, educating and entrancing their young audience with their symbiotic personalities and their proclivity for song, dance, and the joy of silliness. But as iconic as their television personas were, relatively little inside knowledge has been revealed about Lewis herself and the life-changing moments that led her to the entertainment industry and perhaps, most importantly, to Lamb Chop. Renowned for her skills as a performer, Lewis was an equally skilled businesswoman. Operating in an era when women were largely left out of the conversation, she was one of the few women to run her own television production company. Whether it was singing, dancing, conducting, writing, drawing, or ventriloquism-a skill in which she was virtually unmatched-Lewis spent the entirety of her 65 years in pursuit of performative perfection. Constantly innovating and adapting to the needs of her audience and the market, Lewis extended the longevity of her career decade after decade. Her contributions, and that of Lamb Chop, and the rest of her puppet pals forever changed the history of children's television. Now, two decades after Lewis and Lamb Chop last graced television with their presence, Lewis' daughter Mallory and author Nat Segaloff have set the record straight about the iconic pair in Shari Lewis and Lamb Chop: The Team that Changed Children's Television. In this seminal biography, the pair pull the veritable wool from the eyes of audiences who adored the legendary entertainer to examine the joys, sorrows, triumphs, and sheer hard work that gave Lewis and Lamb Chop their enduring star power"--